PENGARUH BRAND AWARENESS, PERCEIVED QUALITY DAN BRAND ASSOCIATION TERHADAP KEPUTUSAN PEMBELIAN ULANG SMARTPHONE SAMSUNG (STUDI KASUS PADA PENGGUNA SMARTPHONE SAMSUNG DI KOTA PADANG) - Arivetullatif, Arivetullatif (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
This study aims to determine how much influence brand awareness, perceived, and brand association has on Samsung Smartphone repurchase decisions in the city of Padang. The population in this study is unknown in number, with a sample of people who have had a Samsung Smartphone, the sample was taken using, accidental sampling. Instrument testing is done by validity test and reliability test. Data analysis using multiple linear regression analysis, and hypothesis testing. The results of this study indicate that Brand awareness has a significant influence on the decision to repurchase Samsung Smartphone in Padang city with sig = 0.032, Perceived quality has a significant influence on the decision to repurchase Samsung Smartphone in Padang with sig = 0.001, Brand association has an significant to the decision to repurchase Samsung Smartphone in the city of Padang with sig = 0,000.